2017
DOI: 10.1111/desc.12564
|View full text |Cite
|
Sign up to set email alerts
|

The specificity of the neural response to speech at birth

Abstract: In this work we ask whether at birth, the human brain responds uniquely to speech, or if similar activation also occurs to a non-speech surrogate 'language'. We compare neural activation in newborn infants to the language heard in utero (English), to an unfamiliar language (Spanish), and to a whistled surrogate language (Silbo Gomero) that, while used by humans to communicate, is not speech. Anterior temporal areas of the neonate cortex are activated in response to both familiar and unfamiliar spoken language,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 28 publications
(74 reference statements)
4
52
1
Order By: Relevance
“…To become a successful language learner, the infant must be able to distinguish and attend to communicatively meaningful signals–speech in particular–among a range of sounds in the environment. To date, research has shown that typically-developing infants with NH prefer speech over: filtered speech (Spence & DeCasper, 1987), noise (Butterfield & Siperstein, 1970), synthetic sine-waves (Vouloumanos & Werker, 2004, 2007), silence (Houston, Pisoni, Kirk, Ying, & Miyamoto, 2003), other naturally occurring sounds (Shultz & Vouloumanos, 2010), and even a whistled surrogate form of language (May, Gervain, Carreiras, & Werker, 2017 Online advance). For example, infants from 1 day to 7 months old show a preference for natural speech over sinewave, as measured by sucking rate and looking time (Vouloumanos & Werker, 2004, 2007).…”
Section: Attention To Speechmentioning
confidence: 99%
See 1 more Smart Citation
“…To become a successful language learner, the infant must be able to distinguish and attend to communicatively meaningful signals–speech in particular–among a range of sounds in the environment. To date, research has shown that typically-developing infants with NH prefer speech over: filtered speech (Spence & DeCasper, 1987), noise (Butterfield & Siperstein, 1970), synthetic sine-waves (Vouloumanos & Werker, 2004, 2007), silence (Houston, Pisoni, Kirk, Ying, & Miyamoto, 2003), other naturally occurring sounds (Shultz & Vouloumanos, 2010), and even a whistled surrogate form of language (May, Gervain, Carreiras, & Werker, 2017 Online advance). For example, infants from 1 day to 7 months old show a preference for natural speech over sinewave, as measured by sucking rate and looking time (Vouloumanos & Werker, 2004, 2007).…”
Section: Attention To Speechmentioning
confidence: 99%
“…In addition, Houston et al (2003) found that 6- and 9-month-old NH infants attend longer to speech sounds such as [hɑp] than to silence. Moreover, a recent study showed that the temporal and frontal areas of the brain are activated in newborns in response to familiar and unfamiliar spoken languages, but not to a whistled surrogate form (May et al, 2017 Online advance). These findings suggest that attention to speech, as well as the neural specificity for spoken language, is innate or developed from in utero auditory experience.…”
Section: Attention To Speechmentioning
confidence: 99%
“…Further evidence that infants are born prepared to learn from speech can be found in neuroimaging studies that reveal cortical networks prepared for linguistic signals from birth. For example, neonatal to 3-month-old infants recruit the same cortical areas for processing speech stimuli as do adults (Dehaene-Lambertz et al, 2006), and these areas respond selectively to speech and not nonspeech (May, Gervain, Carreiras, & Werker, 2017;Peña et al, 2003;Shultz, Vouloumanos, Bennett, & Pelphrey, 2014). This suggests that the foundation of the speech-specific network is present early.…”
Section: Fetal and Neonatal Perceptual Experiencesmentioning
confidence: 99%
“…Infants’ equal looking to the two ethnicities when paired with both backwards languages is taken as evidence that infants do not show a broader association between any unfamiliar sound with unfamiliar faces. However, previous studies have shown that backwards speech is not perceived as language, even by young infants (Dehaene‐Lambertz, Dehaene, & Hertz‐Pannier, ; May et al, ; Peña et al, ; Ramus, Hauser, Miller, Morris, & Mehler, )—thus it is still unclear whether infants may associate any unfamiliar language with any unfamiliar ethnicity.…”
mentioning
confidence: 98%
“…At birth, infants show a preference for listening to speech over nonspeech (Vouloumanos & Werker, ) and can discriminate the language(s) heard in utero from rhythmically distinct unfamiliar languages (Byers‐Heinlein, Burns, & Werker, ; Mehler et al, ; Nazzi, Bertoncini, & Mehler, ). Moreover, infants show different patterns of neural activation in response to native versus non‐native language soon after birth; patterns that become more distinct across the first months of life (May, Byers‐Heinlein, Gervain, & Werker, ; May, Gervain, Carreiras, & Werker, ; Minagawa‐Kawai et al, ; Sato et al, ; Vannasing et al, ). By 4 months, infants prefer their native language to a rhythmically similar non‐native language (Bosch & Sebastián‐Gallés, ; Molnar, Gervain, & Carreiras, ; Nazzi, Jusczyk, & Johnson, ), and by 5 months even prefer speakers of their native language over speakers of an unfamiliar language (Kinzler, Dupoux, & Spelke, ).…”
mentioning
confidence: 99%